Application of Character Education in Rusmee Sthapana School Mayo, Pattani Thailand - Pernando, Danilo; Abdurrahman, Abdurrahman (Journal of English Language and Education, 2025)
This study aims to explore the strategies for implementing character education at Rusmee Sthapana School in Mayo, Pattani, Thailand region predominantly inhabited by a Muslim minority. The school integrates Islamic values and local cultural traditions into its educational practices. Employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation, involving school principals, teachers, students, and community members.The findings indicate that character education at the school is implemented holistically and contextually. Key strategies include the integration of character values into classroom instruction, daily habituation through morning halaqah and congregational prayers, role modeling by teachers and school leaders, active participation of parents and the surrounding community, as well as observation-based non-academic assessments. These practices are in line with Thomas Lickona’s (2018) framework of moral knowing, moral feeling, and moral action, and reflect the competencies of 21st-century learning as outlined by Trilling and Fadel (2016). This study contributes to the discourse on contextually grounded character education models rooted in religious and cultural values within multicultural educational settings.